Does Aggressive Variant Histology Without Invasive Features Predict Overall Survival in Papillary Thyroid Cancer?: A National Cancer Database Analysis. Issue 3 (September 2021) - Limberg, Jessica; Ullmann, Timothy M.; Stefanova, Dessislava; Buicko, Jessica L.; Finnerty, Brendan M.; Zarnegar, Rasa; Fahey, Thomas J.; Beninato, Toni
Abstract : Objective: We aimed to clarify whether aggressive histology of papillary thyroid cancer (PTC) impacts overall survival (OS). Summary Background Data: Aggressive variants of PTC (AVPTC) are associated with invasive features. However, their behavior in the absence of these features is not well characterized. Methods: Patients treated from 2004 to 2015 for classic PTC (cPTC) or AVPTCs were identified from the National Cancer Database. Patients were further stratified based on presence of at least 1 invasive feature—extrathyroidal extension, multifocality, lymphovascular invasion, nodal or distant metastasis. Demographics, treatments, and OS were compared. Results: A total of 170, 778 patients were included—162, 827 cPTC and 7951 AVPTC. Invasive features were more prevalent in AVPTC lesions compared to cPTC (70.7% vs 59.7%, P < 0.001). AVPTC included tall cell/columnar cell (89.5%) and diffuse sclerosing (10.5%) variants. Patients with invasive features had worse OS irrespective of histology. Furthermore, when controlling for demographics, tumor size, and treatment variables in patients with noninvasive lesions, AVPTC histology alone was not associated with worse OS compared to cPTC ( P = 0.209). In contrast, among patients who had at least 1 invasive feature, AVPTC histology was independently predictive of worse OS ( P < 0.05) {TCV/Columnar hazard ratio [HR] 1.2; [95% confidence interval (CI) 1.1–1.3] and diffuse sclerosing HR 1.3; 95% CI 1.0–1.7]}. All invasive features, except multifocality, were independently associated with worse OS, with metastasis being the most predictive [HR 2.9 (95% CI 2.6–3.2) P < 0.001]. Conclusions: In the absence of invasive features, AVPTC histology has similar OS compared to cPTC. In contrast, diffuse sclerosing and tall cell/columnar variants are associated with worse OS when invasive features are present.